Gender Stereotype: Being Nepali Women! - K.C., Priyanka; Pasa, Rajan Binayek; Khatri, Bishnu Bahadur (Patan Pragya, 2022)
This paper discusses gender stereotypes still embedded in Nepali society towards women due to the disbelief and misconception which shaping the expectations, attitudes, and behaviors toward women. This study also elucidates the sad reality of gender stereotype throughout the life of women (birth, marriage etc.) that have been practicing in the culture and making life vulnerable and challenging. The critical appraisal at the situation of Nepali women reveals a terrible realityas women are still tolerating gender stereotype practices in the society, even when everyone is aware of their rights and gender equality. In particular, some exceptional woman personalities such as Pasang Lhamu Sherpa (first Nepali woman and the second woman in the world to summit Mount Everest); Anuradha Koirala (CNN's Hero of the Year-2010); Puspa Basnet (CNN's Hero of the Year-2012) etc. are the epitome of rebellers of the gender stereotype in Nepal. In general, equal praise, motivation and right education to both child (son and daughter) starting from home can help them to build gender neutral attitude in the future. Therefore, capacity to defy all the odds of the society like these rebellers of stereotype and gender neutral attitude towards gender stereotypes are the foundation of way out for maintaining gender equality in Nepali society.